Calendar of Events. (Communications of the ACM, 2015)
A calendar of events related to computer science for October 2015 is presented which includes PACT ‘15: International Conference on Parallel Architectures and Compilation, CIKM’15: 24 ACM International Conference on Information and Knowledge Management, and SPLASH ‘15: Conference on Systems, Programming, Languages, and Applications: Software for Humanity.